Glass ceramic and preparation method thereof
A glass ceramic composition with two crystallized glasses and a high softening point flux adjusts sintering temperature and shrinkage behavior, addressing the mismatch between ceramic formula and conductor paste in LTCC materials, achieving low-temperature sintering and controlled dielectric properties for LTCC materials.
Patent Information
- Application Number
- CN202211729257.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-12-30
AI Technical Summary
There is a lack of systematic research on the matching between ceramic formula composition and conductor paste in low temperature co-fired ceramic (LTCC) materials, leading to high sintering temperatures that are not conducive to matching with conductor pastes and limiting the development of LTCC materials.
A glass ceramic composition comprising two types of crystallized glasses and a high softening point flux, along with a specific skeleton material, is used to adjust sintering temperature and shrinkage behavior, allowing for low-temperature sintering with silver conductor pastes, achieving a dense LTCC material with controlled dielectric properties.
The glass ceramic enables low-temperature sintering at 860°C, resulting in a dielectric constant of 18.6-23.7 and a Q value greater than 3000 under 24GHz, while maintaining low dielectric loss and preventing defects during co-firing with silver.
Smart Images

Figure CN116023032B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic devices and low-temperature co-fired ceramic substrates, and in particular relates to a glass ceramic and a preparation method thereof. Background Art
[0002] In recent years, microwave technology has been developing towards higher frequencies, and while expanding the bandwidth and making full use of the bandwidth resources, mobile communications and portable terminals are developing towards miniaturization, integration, lightness, high reliability and low cost. The multilayer structure design based on low temperature co-fired ceramic (LTCC) technology provides a solution to achieve this goal, and it has a wide range of applications in electronic packaging, radio frequency devices and automotive electronics.
[0003] At present, there is almost no research on the matching of LTCC powder materials and conductor pastes. There is a lack of systematic research on the matching between ceramic formula composition and conductor paste. Therefore, the development law of LTCC materials has not been fully understood.
[0004] In patent CN 109796136, due to the use of a single glass sintering aid, the sintering temperature is high (900°C), which is not conducive to matching with the conductor paste. Because of its high sintering temperature, the patent also lacks data on conductor paste matching, and only stays at a single material index. This is also a unified problem in LTCC material research. Summary of the invention
[0005] The purpose of the present invention is to overcome the above-mentioned shortcomings of the prior art and provide a glass ceramic and a preparation method thereof to solve the problem in the prior art that ceramic formula powder and conductor slurry are difficult to match.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A glass ceramic, comprising glass, flux and skeleton material; the mass proportion of the glass is 3.75-20%, the mass proportion of the skeleton material is 80-95%, and the balance is flux;
[0008] The glass is composed of a mixture of C crystallized glass and Z crystallized glass;
[0009] The skeleton material consists of LZT and CT;
[0010] The flux is an oxide.
[0011] A further improvement of the present invention is:
[0012] Preferably, the C crystallized glass comprises, by mass fraction, 30%-40% CaO, 20-40% B2O3, 30-40% SiO2, and 0-5% ZrO2, P2O5, Al2O3, MgO, La2O3 or TiO2.
[0013] Preferably, in terms of mass fraction, the Z crystallized glass is 50% ZnO and 50% of a mixture, the mixture is a mixture of B2O3 and SiO2, and the mass ratio of B2O3 to SiO2 in the mixture is 4.6-40.7.
[0014] Preferably, the flux is at least one oxide selected from the group consisting of ZnO, MnO2, Cr2O3, Li2O, P2O5, Bi2O3 and CuO.
[0015] Preferably, the LZT is a mixture of Li2CO3, ZnO and TiO2 in a molar ratio of 1:1:3.
[0016] Preferably, the CT is a mixture of CaO and TiO2 in a molar ratio of 1:1.
[0017] A method for preparing the above-mentioned glass ceramics, preparing C crystalline glass powder and Z crystalline glass powder respectively by glass melting method, and preparing LZT skeleton material and CT skeleton material respectively by solid phase reaction method;
[0018] A glass ceramic powder is prepared by mixing a crystallized glass powder, a skeleton material and a flux according to a mass ratio, a tape casting slurry is prepared from the glass ceramic powder, a green ceramic tape is prepared from the tape casting slurry, and a LTCC ceramic block is prepared from the green ceramic tape.
[0019] Preferably, the melting temperature of the C crystallized glass powder and the Z crystallized glass powder is 1200-1350° C., and the melting time is 1-4 hours.
[0020] Preferably, the preparation process of the LZT framework material and the CT framework material is to place the raw materials in a ball mill, obtain a mixture after ball milling, and obtain the framework material after drying, sieving and pre-calcining the mixture.
[0021] Preferably, the pre-burning temperature of the LZT skeleton material is 850-900° C., and the pre-burning time is 2-8 hours; the pre-burning temperature of the CT skeleton material is 950-1050° C., and the pre-burning time is 2-8 hours.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The invention discloses a glass ceramic material, which is composed of two kinds of crystallized glasses, a high softening point flux and a skeleton material, and is a typical glass ceramic. By adjusting the types and proportions of C and Z crystallized glasses and the high softening point flux, the sintering temperature can be adjusted, and the shrinkage behavior of the glass ceramic co-fired with silver can be synchronously controlled, so that the sintering temperature and the shrinkage behavior can be controlled simultaneously. In addition, the dielectric constant temperature coefficient of the glass ceramic can be adjusted by the weight ratio of LZT to CT in the skeleton material. By adjusting the formula, a LTCC material can be obtained which is sintered densely at 860°C, has a dielectric constant of 18.6-23.7 under the condition of 24GHz, and a Q value greater than 3000.
[0024] The invention also discloses a method for preparing a glass ceramic material. The method prepares a ceramic block by a conventional preparation method, and the whole process is easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the DSC diagram of C crystal glass;
[0026] Figure 2 This is the DSC graph of Z crystal glass;
[0027] Figure 3 This is the SEM image of the GS30 surface;
[0028] Figure 4 This is the SEM image of the cross section of GSA30 co-fired with silver. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0030] The invention discloses a glass ceramic, which comprises glass, a high softening point flux and a skeleton material. In terms of mass fraction, the mass proportion of the glass is 3.75-20%, the mass proportion of the skeleton material is 80-95%, and the balance is the high softening point flux.
[0031] The glass is composed of two kinds of crystallized glasses, namely C glass and Z glass. The C crystallized glass is composed of 30%-40% CaO, 20-40% B2O3, 30-40% SiO2, and 0-5% ZrO2, P2O5, Al2O3, MgO, La2O3 or TiO2 in a weight ratio. The Z crystallized glass is composed of 50% ZnO and 50% of a mixture of B2O3 and SiO2 in a weight ratio of 4.6-40.7.
[0032] In the glass-ceramics of the present invention, the high softening point flux contains at least one oxide of ZnO, MnO2, Cr2O3, Li2O, P2O5, Bi2O3 or CuO.
[0033] The glass ceramic skeleton material in the present invention is composed of the following: the compound group is Li2O-ZnO-CaO-TiO2, which can be combined into LZT and CT. LZT is specifically composed of Li2O-ZnO-TiO2 to form Li2ZnTi3O8 (the molar ratio of Li2CO3, ZnO and TiO2 is 1:1:3), and CT is specifically composed of CaO-TiO2 to form CaTiO3 (the molar ratio of CaO to TiO2 is 1:1).
[0034] For dielectric ceramic materials, glass is generally added to achieve low-temperature sintering, which easily deteriorates the overall dielectric properties. Glass is an amorphous solid with an irregular structure, which is prone to ion conduction, ion vibration, and changes in alkali metals, OH-, etc., which leads to an increase in the dielectric loss of the material. In order to achieve low-temperature sintering while maintaining low dielectric loss, a common solution is to add crystalline glass as a flux.
[0035] During the co-firing process of low-temperature co-fired ceramics, organic components such as binders are usually removed during the deesterification process before the materials are sintered and densified. The difficulty in sintering ceramic substrates with silver as line conductors lies in the simultaneous sintering of two heterogeneous materials - silver and ceramics. There are three key technical points. The first is to control the sintering shrinkage and the overall change of the substrate; the second is to control the sintering shrinkage behavior of the two materials to avoid microscopic and macroscopic defects; the third is to achieve the discharge of the binder during the sintering process.
[0036] As a method to stabilize the shrinkage behavior, adding two or more glass materials with different softening points to low-temperature co-fired ceramics is a very feasible path. Since the shrinkage of low-temperature co-fired ceramics depends on the softening behavior of several glasses, a gentle shrinkage curve can be obtained. In addition, this method can also prevent glass bubbling and control shrinkage behavior. In particular, if a flux with a high softening point is added, a path is opened for the gas released by the decomposition of the binder during sintering, which is very effective in reducing the residual carbon in low-temperature co-fired ceramics.
[0037] The glass ceramic prepared by the present invention can be well co-fired with silver conductor slurry.
[0038] The present invention also provides a method for preparing the above glass ceramic material, the specific steps are as follows:
[0039] In the present invention, C and Z crystallized glass powders can be prepared by conventional glass melting methods. Specifically, the process of preparing the crystallized glass powder may include: calculating the weight (wt%) of various raw materials required according to the C and Z crystallized glass ratios (wt%), and mixing the ingredients, wherein the C crystallized glass is composed of 30%-40% CaO, 20-40% B2O3, 30-40% SiO2, and 0-5% ZrO2, P2O5, Al2O3, MgO, La2O3 or TiO2 in a weight ratio. The Z crystallized glass is composed of 50% ZnO, 50% B2O3 and SiO2 in a weight ratio of 4.6-40.7, and the mixture is mixed to obtain a mixture, and the raw material mixture is melted and quenched to obtain glass fragments; the glass fragments are ground, dried, and sieved to obtain the C and Z crystallized glass powders. The purity of the raw materials used is greater than 99.5%. The use of raw materials with a purity greater than 99.5% to prepare C and Z glass powders can ensure the stability of the glass crystallization phase and reduce the influence of impurities on dielectric properties. The melting system can be: 1200-1350°C, preferably 1250-1350°C; 1-4 hours. Before melting, an appropriate amount of water can be added to mix the raw materials evenly. When quenching, the molten glass can be quickly poured into deionized water for quenching.
[0040] The present invention can obtain Li2ZnTi3O8 skeleton material by solid phase reaction method. Specifically, the process of preparing Li2ZnTi3O8 ceramic powder may include: placing Li source (such as lithium carbonate Li2CO3), Zn source (such as zinc oxide ZnO), and Ti source (titanium dioxide such as TiO2) in a 10L vertical ball mill according to the chemical formula of Li2ZnTi3O8, adding zirconium oxide balls and deionized water, and milling for 2-8 hours at a stirring speed of 200r / min-300r / min to obtain a raw material mixture LZT; drying and sieving the raw material mixture LZT, placing it in a pre-sintering furnace and pre-sintering it at 850-900°C for 2-8 hours for use.
[0041] The main process for preparing the CaTiO3 skeleton material in the present invention is the same as the preparation method of the Li2ZnTi3O8 skeleton material, the only difference being that the pre-firing temperature is 950-1050°C (eg 1000°C) and the pre-firing time is 2-8H.
[0042] Next, glass powder, high softening point flux and skeleton material are mixed in mass proportion to prepare glass ceramic powder. The mixing method can be ball milling, where the glass ceramic powder is added to an alumina tank in a ratio of material: ball: anhydrous ethanol = 1:3:2, and ball milled in a planetary ball mill for 1 to 4 hours.
[0043] Toluene, ethanol, polyvinyl butyral and dioctyl phthalate are added to the glass ceramic powder, and the mixture is evenly mixed by ball milling in a closed environment, and vacuum degassing is performed to obtain a tape casting slurry of low temperature co-fired ceramics, and the tape casting slurry is injected into a tape casting machine to form a thin layer of green ceramic tape, and after drying, a dense green ceramic tape is formed;
[0044] The dried green porcelain tape is cut into the required shape, stacked into blocks, and placed in an isostatic machine under the conditions of 70°C and 20MPa, and the pressure is maintained for 10 minutes. Then, it is placed in an electric furnace for sintering. The specific conditions are: the green porcelain tape is heated from room temperature to 450°C at a rate of 2°C / min, and kept warm for 2 hours for debinding; the green porcelain tape after debinding is heated from 450°C to 730°C at a rate of 3°C / min, and kept warm for 30 minutes to allow the C glass to fully crystallize, and then heated to 860°C at a rate of 3°C / min, and kept warm for 60 minutes to sinter into a LTCC ceramic block, and the dielectric constant and dielectric loss are tested under 24GHZ conditions.
[0045] At the same time, the dried raw porcelain tape is cut into the required shape, printed with 1091L silver paste, stacked into blocks and placed in an isostatic press. The isostatic pressing and sintering conditions are the same as those of the sintered LTCC multilayer. The co-firing state of silver is visually inspected, the warpage is detected by a laser thickness gauge, and the surface grain uniformity and cross-section porosity are detected by scanning electron microscopy.
[0046] The present invention provides a glass ceramic and a preparation method thereof. Experimental results show that by adjusting the formula, a LTCC material can be obtained which is sintered densely at 860°C, has a dielectric constant of 18.6-23.7 and a Q value greater than 3000 under the condition of 24GHz, and the preferred formula can be co-fired with a silver conductor paste.
[0047] In order to further understand the present invention, the glass ceramics provided by the present invention are described in detail below in conjunction with the embodiments, and the protection scope of the present invention is not limited by the following embodiments.
[0048] Example 1
[0049] (A) C Crystallized Glass Preparation
[0050] A raw material mixture was obtained by mixing 785.2g CaCO3, 329.8g B2O3, 329.9g SiO2, 8.6g ZrO2, 11.5g P2O5, 12.0g Al2O3, 7.7g MgO, 7.7g La2O3, and 7.7g TiO2. After melting at 1300°C for 2 hours, it was poured into deionized water and quenched to obtain glass fragments. After filtering the water from the glass block, it was placed in a 10L vertical ball mill, 10kg of 5mm diameter zirconium oxide balls and 2KG deionized water were added, and the ball mill was carried out at a stirring speed of 250r / min for 4 hours. Finally, the glass slurry was sieved and dried to obtain glass powder with a particle size of 2-3μm. The glass DSC showed Figure 1 .
[0051] (B) Preparation of Z crystal glass
[0052] A mixture is obtained by mixing 1000g ZnO, 900g B2O3 and 100g SiO2. The Z glass flakes and glass powder are prepared in the same manner. The DSC of the glass is shown in FIG. Figure 2 .
[0053] (C) Preparation of skeleton material LZT
[0054] Mix 280.3g Li2CO3, 309.1g ZnO and 910.5g TiO2, place in a 10L vertical ball mill, add 10kg zirconia balls with a diameter of 5mm, add 2KG deionized water, and ball mill for 4 hours at a stirring speed of 250r / min to obtain a raw material mixture LZT; dry and sieve the raw material mixture LZT, and pre-calcine it at 900℃ for 4 hours to obtain the skeleton material for later use.
[0055] (D) CT preparation of skeleton materials
[0056] Mix 833.8g CaCO3 and 666.2g TiO2, place in a 10L vertical ball mill, add 10kg zirconia balls with a diameter of 5mm, add 2KG deionized water, and ball mill for 4 hours at a stirring speed of 250r / min to obtain a raw material mixture CT; dry and sieve the raw material mixture CT, and pre-calculate it at 1000℃ for 4 hours to obtain the skeleton material for later use.
[0057] (E) Preparation of glass ceramics
[0058] Next, glass, auxiliary components and skeleton materials were mixed according to the proportions in Table 1 to prepare multiple glass ceramic powders G1-G30. The amount of a single test powder was 100 g. 150 g of anhydrous ethanol and 300 g of 10 mm zirconia balls were added. All were placed in an alumina can and milled in a planetary ball mill for 1 h at a speed of 250 r / min.
[0059] Table 1 Glass ceramic formula powder corresponding to specific embodiments
[0060]
[0061]
[0062] (F) Preparation of green porcelain tape
[0063] Take 80g of glass ceramic powder, add 13g of toluene, 13g of ethanol, 7g of polyvinyl butyral, 4g of dioctyl phthalate, and 300g of 10mm zirconium balls, add them into an alumina can, and discharge the material after ball milling in a planetary ball mill for 1h (speed is 150r / min), and then vacuum degassing to obtain a low-temperature co-fired ceramic tape. The tape-casting ceramic slurry is injected into the tape-casting machine to form a thin layer of green porcelain tape. After drying, a green porcelain tape GS1-GS30 with a thickness of 130um is obtained.
[0064] (G) LTCC ceramic block preparation and measurement
[0065] The GS1-GS30 raw ceramic tape was cut into 60×60mm, stacked into 8 layers of blocks, and then placed in an isostatic machine under 70℃, 20MPa conditions, pressure maintained for 10min, and then placed in an electric furnace for sintering. The specific conditions are: the raw ceramic tape was heated from room temperature to 450℃ at a rate of 2℃ / min, and kept warm for 2h for debinding; the raw ceramic tape after debinding was heated from 450℃ to 730℃ at a rate of 3℃ / min, kept warm for 30min to allow C glass to fully crystallize, and then heated to 860℃ at a rate of 3℃ / min, kept warm for 60min to sinter into multiple LTCC ceramic blocks, GSF1-GSF30. The dielectric constant and dielectric loss were measured at a resonant frequency of 24GHZ, and the Q value was judged to be good for more than 2000. The GSF21 and GSF22 ceramic blocks were not sintered densely.
[0066] (H) The measuring equipment and measuring conditions are as follows.
[0067] Network Analyzer, P5008A
[0068] Resonator: with built-in fixture (resonant frequency: 24GHZ)
[0069] Before the measurement, the network analyzer was connected and the cable loss was calibrated.
[0070] (I) LTCC multilayer preparation and testing
[0071] At the same time, GS1-GS30 took 4 pieces of green porcelain tapes to print 1091L silver paste of Xi'an Hongxing Electronic Paste Technology Co., Ltd., stacked them into 4 layers of blocks and placed them in an isostatic machine. They were pressurized at 70℃ and 20MPa. After holding the pressure for 10 minutes, they were cut into 60mm×60mm and then placed in an electric furnace for sintering to obtain multiple LTCC multilayers GSA1-GSA30. The LTCC multilayers co-fired with silver were visually inspected for diffusion, and the warpage was detected with a laser thickness gauge. At the same time, a scanning electron microscope was used to detect the surface grain uniformity and the degree of cross-section porosity.
[0072] Table 2 LTCC ceramic block and multilayer test data Table 2
[0073]
[0074] According to the results in Table 2, the ceramic block of the glass ceramic of the present invention has excellent dielectric properties, the optimal formula Q value reaches more than 3000, and the surface grains of GS30 are Figure 3 At the same time, the combination of two crystallized glasses and the addition of a high softening point flux can greatly improve the diffusion and warping problems of co-firing with silver. The SEM cross section of GSA30 co-firing with silver shows Figure 4 This glass ceramic has high practical value for the production of LTCC substrates and devices.
[0075] Embodiment 31
[0076] In this embodiment, the mass proportion of CaO in the C crystallized glass is 35%, the mass proportion of B2O3 is 32%, the mass proportion of SiO2 is 30%, and the balance is ZrO2. The other parts not involved are the same as those in Example 1.
[0077] Embodiment 32
[0078] In this embodiment, the mass proportion of CaO in the C crystallized glass is 30%, the mass proportion of B2O3 is 40%, the mass proportion of SiO2 is 30%, and the remaining parts not involved are the same as those in Example 1.
[0079] Embodiment 33
[0080] In this embodiment, the mass proportion of CaO in the C crystallized glass is 40%, the mass proportion of B2O3 is 23%, the mass proportion of SiO2 is 35%, and the balance is Al2O3. The other parts not involved are the same as those in Example 1.
[0081] Embodiment 34
[0082] In this embodiment, the mass proportion of CaO in the C crystallized glass is 30%, the mass proportion of B2O3 is 25%, the mass proportion of SiO2 is 40%, and the balance is MgO. The other parts not involved are the same as those in Example 1.
[0083] Embodiment 35
[0084] In this embodiment, the mass proportion of CaO in the C crystallized glass is 39%, the mass proportion of B2O3 is 20%, the mass proportion of SiO2 is 40%, and the balance is La2O3. The other parts not involved are the same as those in Example 1.
[0085] Embodiment 36
[0086] In this embodiment, the mass proportion of CaO in the C crystallized glass is 30%, the mass proportion of B2O3 is 34%, the mass proportion of SiO2 is 32%, and the balance is TiO2. The remaining parts not involved are the same as those in Example 1.
[0087] Embodiment 37
[0088] In this embodiment, the melting temperature of C crystallized glass and Z crystallized glass is 1200° C., the melting time is 4 hours, and the rest of the parts not involved are the same as those in Embodiment 1.
[0089] Embodiment 38
[0090] In this embodiment, the melting temperature of C crystallized glass and Z crystallized glass is 1350° C., the melting time is 1 hour, and the rest of the parts not involved are the same as those in Embodiment 1.
[0091] Embodiment 39
[0092] In this embodiment, the melting temperature of C crystallized glass and Z crystallized glass is 1250° C., the melting time is 3 hours, and the rest of the parts not involved are the same as those in Embodiment 1.
[0093] Embodiment 40
[0094] In this embodiment, the melting temperature of C crystallized glass and Z crystallized glass is 1300° C., the melting time is 3 hours, and the other parts not involved are the same as those in Embodiment 1.
[0095] Embodiment 41
[0096] In this embodiment, the pre-burning temperature of LZT is 850° C., the pre-burning time is 8 hours, and the rest of the parts not involved are the same as in Embodiment 1.
[0097] Embodiment 42
[0098] In this embodiment, the pre-burning temperature of LZT is 880° C., the pre-burning time is 3 h, and the rest of the parts not involved are the same as in Embodiment 1.
[0099] Embodiment 43
[0100] In this embodiment, the pre-burning temperature of CT is 950° C., the pre-burning time is 6 hours, and the rest of the parts not involved are the same as those in Embodiment 1.
[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A glass ceramic, characterized in that: It includes glass, flux and skeleton material; the mass proportion of the glass is 3.75-20%, the mass proportion of the skeleton material is 80-95%, and the balance is flux; The glass is composed of a mixture of C crystallized glass and Z crystallized glass; The skeleton material consists of LZT and CT; The flux is an oxide; The composition of the C crystallized glass is 30%-40% CaO, 20-40% B2O3, 30-40% SiO2, and 0-5% ZrO2, P2O5, Al2O3, MgO, La2O3 or TiO2 by mass fraction; In terms of mass fraction, the Z crystallized glass is a mixture of 50% ZnO and 50% B2O3 and SiO2, and the mass ratio of B2O3 to SiO2 in the mixture is 4.6-40.7; The flux is at least one oxide selected from ZnO, MnO2, Cr2O3, Li2O, P2O5, Bi2O3 or CuO; The LZT is a mixture of Li2CO3, ZnO and TiO2 in a molar ratio of 1:1:3; The CT is a mixture of CaO and TiO2 in a molar ratio of 1:
1.
2. A method for preparing the glass ceramic according to claim 1, characterized in that: C crystalline glass powder and Z crystalline glass powder were prepared by glass melting method, and LZT skeleton material and CT skeleton material were prepared by solid phase reaction method. A glass ceramic powder is prepared by mixing a crystallized glass powder, a skeleton material and a flux according to a mass ratio, a tape casting slurry is prepared from the glass ceramic powder, a green ceramic tape is prepared from the tape casting slurry, and a LTCC ceramic block is prepared from the green ceramic tape.
3. The method for preparing glass ceramics according to claim 2, characterized in that: The melting temperature of the C crystallized glass powder and the Z crystallized glass powder is 1200-1350° C., and the melting time is 1-4 hours.
4. The method for preparing glass ceramics according to claim 2, characterized in that: The preparation process of the LZT skeleton material and the CT skeleton material is as follows: placing the raw materials in a ball mill, obtaining a mixture after ball milling, and obtaining the skeleton material after drying, sieving and pre-calcining the mixture.
5. The method for preparing glass ceramics according to claim 2, characterized in that: The pre-burning temperature of LZT skeleton material is 850-900℃, and the pre-burning time is 2-8h; the pre-burning temperature of CT skeleton material is 950-1050℃, and the pre-burning time is 2-8h.
